Enzymatic stoichiometry reveals phosphorus limitation-induced changes in the soil bacterial communities and element cycling: Evidence from a long-term field experiment - Cui, Jiwen; Zhang, Shuai; Wang, Xiya; Xu, Xinpeng; Ai, Chao; Liang, Guoqing; Zhu, Ping; Zhou, Wei (Geoderma, 2022)
[Display omitted] •Nitrogen (N) fertilizer increased microbial phosphorus (P) limitation.•Long-term application of organic fertilizers resulted in microbial N limitation.•Microbial P limitation drove shifts in bacterial community structure.•Microbial P limitation promoted the decomposition of labile organic matter.•Microbial P limitation directly affected soil N and P cycling. Soil microbial growth and activity are generally limited by availability of resources such carbon (C), nitrogen (N), or phosphorus (P) in terrestrial ecosystems. However, how soil microbial response to resource limitation in intensive agricultural ecosystems is unclear. Four treatments, namely no fertiliser (CK), chemical fertiliser (NPK), only N fertiliser (N), and organic fertiliser with chemical fertiliser (MNPK), were selected to investigate the effects of different fertiliser practices on the pattern and degree of the limitation of soil microorganisms by elemental availability. The enzyme stoichiometry results indicated that under CK, NPK, and N fertiliser treatments, the soil microbial community as a whole was limited by the availability of C and P. N fertiliser application alone (N) considerably increased the limitation degree of P availability by soil microorganisms, which was caused by the increase in soil N/P. The increased microbial P limitation significantly increased the relative abundance of copiotrophic taxa (Actinobacteria and Sphingomonas) that use labile carbonaceous compounds (such as starch), whereas it significantly decreased the relative abundance of oligotrophic taxa (Acidobacteria and RB41) that use recalcitrant carbonaceous compounds (such as lignin, pectin, and hemicellulose) and important ratios of the microbial community structure (the ratio of fungi/bacteria and the ratio of gram-positive/negative bacteria). Changes in the microbial community structure may be unfavourable for the increase in soil organic matter originating from microorganisms (such as fungi). As per the partial least squares path modelling, N and P cycling was directly affected by microbial P limitation. Linear regression analysis further indicated that with an increase in P limitation, the abundance of functional genes related to N cycling (N fixation, nitrification, and denitrification), P capture (phosphatase and 3-phytase), and P retention (polyphosphate kinase) increased significantly. These results revealed that microorganisms in a P-limited environment adjust their abundance of functional genes to absorb and retain insufficient element (P) while accelerating the turnover of the excess element (N). This study revealed the status and extent of the resource limitation for soil microbial utilization under different long-term fertilisation regimes and indicated that soil bacterial communities respond to resource limitation by adjusting their community structure and element cycling.